أمن الطريق وأثره في شرط الاستطاعة للحج - القحطاني، مسفر بن علي بن محمد (الجامعة الإسلامية العالمية - مجمع البحوث الاسلامية, 2013)
Capacity to perform duties is the basic condition for the injunctions of the shar ‘ah. This condition is also applicable to the obligation of pilgrimage. Since the qur’an has expressly mentioned the requirement of capacity for performing this onerous obligation and this condition has been reiterated in the Prophet's statements as well, the scholars of Islam have elaborately laid down the rules that define this capacity. They have identified various situations and factors that contribute to the undoing of this capacity and absolving an individual of this obligation pending these factors. These factors are related to the person of the individual as well as to the conditions and circumstances accompanying him during the period of the pilgrimage. The writer explains the variety of factors and circumstances that affect the legal capacity of the individual to perform the obligation of pilgrimage. He has demonstrated by means of different examples that the change in conditions and circumstances is always taken into consideration for determining the capacity of an individual to perform pilgrimage.
Keywords: الشريعة الإسلامية -- فقه العبادات -- الاستطاعة في الحج -- أمن الطريق